Analisis Kinerja Sistem Pengereman Pada Mobil Hemat Energi Asykar Urban Gasoline - Tussalam, Al Fitra; Syafri, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Asykar Urban Gasoline is a car made by students of Riau University within the standard of Kontes Mobil Hemat Energi (KMHE). The car consist of multiple system to run properly such as steering system, electrical system, engine system, transmission system and braking system. This research aim to analyze the braking system, due to its vital role and also effect the fuel consumption of the car. It is done on 2 types of roads: asphalt and concrete (dry and wet) with 3 speed variation of 25 km/h, 35 km/h, 45 km/h. The result show that the highest braking distance on wet asphalt within 45 km/h is 7.96 m theoretically and 7.5 m on field with 5.7% error. Next, braking distance with the biggest range among all data is on the wet asphalt within 35 km/h velocity and braking distance of 4.83 m theoretically and 4.3 m on field with 9.93% error. It means the amount of range in general is not really big which not exceeding 10%. Results also show the stabilization of the car tendto over steer regardless on theoretical calculation or in actual test. Keywords: Brake, Braking Distance, Car Direction Stability